1996
DOI: 10.1021/ja953262n
|View full text |Cite
|
Sign up to set email alerts
|

Use of Deuterium Kinetic Isotope Effects To Probe the Cryptoregiochemistry of Δ9 Desaturation

Abstract: The biological syn-dehydrogenation (desaturation) of fatty acids 1 as exemplified by the ∆9 desaturase-mediated transformation of stearoyl CoA (1) to give oleyl CoA (2) represents one of the more virtuosic displays of enzymatic selectivity. Two classes of desaturases catalyze this intriguing transformation: soluble plant enzymes containing a carboxylate-bridged, nonheme diiron center 2 and less well-characterized, nonheme iron, membrane-bound catalysts as represented by the ∆9 desaturase found in Saccharomyces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
95
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(112 citation statements)
references
References 22 publications
16
95
1
Order By: Relevance
“…The intrinsic hydroxylation activity of desaturases with different regiospecificities makes these enzymes possible targets for future directed evolution experiments. Furthermore, the observation of low level hydroxylation activity at C-12 for the ⌬ 12 desaturase from A. thaliana, C-9 for the ⌬ 9 desaturase of S. cerevisiae, C-5 for the ⌬ 5 desaturase of B. subtilis, and C-15 for the -3 linoleate desaturase from flax suggests that these positions are the sites of initial oxidation of the desaturation reactions, corroborating the kinetic isotope effect studies of Buist and coworkers (19,(32)(33)(34).…”
Section: Discussionsupporting
confidence: 85%
“…The intrinsic hydroxylation activity of desaturases with different regiospecificities makes these enzymes possible targets for future directed evolution experiments. Furthermore, the observation of low level hydroxylation activity at C-12 for the ⌬ 12 desaturase from A. thaliana, C-9 for the ⌬ 9 desaturase of S. cerevisiae, C-5 for the ⌬ 5 desaturase of B. subtilis, and C-15 for the -3 linoleate desaturase from flax suggests that these positions are the sites of initial oxidation of the desaturation reactions, corroborating the kinetic isotope effect studies of Buist and coworkers (19,(32)(33)(34).…”
Section: Discussionsupporting
confidence: 85%
“…It is clear that the presence of a substrate w-F-tag did not significantly affect the pronounced preference of the desaturase system to oxygenate 9-thia substrate analogues as we have previously documented (see Introduction). The ratio of 9-to 10-sulfoxidized products (1.6 : 1) obtained in this work compares favorably with the values obtained from both direct competition (2.1 : 1 [6]) and noncompetitive incubation of thiastearates (1.7 [5]). Good correlation between sulfoxidation ratios derived from experiments with nonfluorinated and w-fluorinated thiastearates have also been obtained for a soluble, plant D9-desaturase system [9] [15].…”
supporting
confidence: 82%
“…However, some important mechanistic information has been obtained on the structurally related yeast enzyme [4], which can be conveniently studied in vivo by an appropriate experimental design. A KIE study showed that the H-atom at C(9) of substrate is removed first in an isotopically sensitive step, followed by rapid cleavage of the CÀH bond at C(10) [5]. This result correlates well with the observation that desaturase-mediated oxo transfer occurs most efficiently when a S-atom occupies the 9-position of a thiastearoyl substrate (Scheme 1, b) [6]; the enantioselectivity of sulfoxidation matches the stereochemistry (syn, pro-R) of the corresponding parent reaction [7] [8].…”
mentioning
confidence: 99%
“…[30] The current data indicate that this overall isotope effect contains a significant secondary KIE component. A strong KIE has also been reported at C12 during D 12 desaturation.…”
Section: Discussionmentioning
confidence: 63%